Penguatan dan Pembinaan Kader Muhammadiyah untuk Peningkatan Keberdayaan Masyarakat di Ranting Pisangan Baru, Jakarta Timur: Strengthening and Coaching of Muhammadiyah Cadre to Increase Community Empowerment in Pisangan Baru, East Jakarta - Wahjusaputri, Sintha; Bunyamin, Bunyamin; Rahmanto, Muhammad Arifin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve the capacity and role of Muhammadiyah branches in empowering the community in Pisangan Baru, Jakarta through structural development and strengthening the skills of cadres. Muhammadiyah branches as the most advanced organizational structure facing the community have a strategic role in driving da'wah, social, and educational activities in the community. However, obstacles such as limited human resources, minimal cadre training, and low community participation often hinder program optimization. The methods of this activity include managerial training, routine mentoring, focus group discussions (FGD) to identify community needs, and evaluation to assess the effectiveness of activities. The results of the activity showed an increase in the managerial and communication skills of cadres, improvements in the organizational structure of the branch, and increased community participation in various activities initiated by Muhammadiyah branches. The obstacles faced included limited time for cadres and the fact that there were still people who did not understand the role of Muhammadiyah branches. Overall, this activity succeeded in increasing the effectiveness of Muhammadiyah branches in empowering the community, Consistent follow-up is needed to maintain the sustainability of the program and strengthen the synergy between Muhammadiyah branches and the community in Pisangan Baru, Matraman East Jakarta.